Psychopedagogical Study of Self-Efficacy and Problem-Solving in Aqidah Akhlak Learning for Sdg 4 - Jiyanto; Desti Widiani; Lilik Istiqomah (Universitas Muhammadiyah Surakarta, 2025)
Objectives: This study aims to assess the self-efficacy levels and problem-solving abilities of ninth-grade students at MTs Muhammadiyah Gemolong in Aqidah Akhlak learning. It also seeks to examine the correlation between self-efficacy and problem-solving abilities, contributing to the achievement of Sustainable Development Goal 4 (Quality Education). Theoretical framework: The research is based on Bandura’s self-efficacy theory and problem-solving theory, applied to the context of Quality Education in Sustainable Development Goal 4. Literature review: Previous studies indicate a positive relationship between self-efficacy and problem-solving skills. However, research specifically examining this in Aqidah Akhlak learning is limited. Method: A quantitative correlational design was used in this study, which involved 87 ninth-grade students at MTs Muhammadiyah Gemolong. A simple random sampling technique selected 71 students as participants. Data were collected using validated self-efficacy questionnaires and problem-solving tests. The data were analyzed using the Kolmogorov-Smirnov normality test and Pearson’s Product-Moment correlation, conducted with SPSS version 26.0. Result: The study found that 66.20% of students had moderate self-efficacy, and 67.61% exhibited moderate problem-solving ability. A significant positive correlation (r = 0.247, p = 0.038) was found between self-efficacy and problem-solving ability, indicating a low but positive relationship between the two variables. Implications: Enhancing self-efficacy can improve problem-solving skills in Aqidah Akhlak learning, supporting the goals of Sustainable Development Goal 4. Novelty: This study provides new insights into the relationship between self-efficacy and problem-solving abilities in Aqidah Akhlak learning, an area with limited research.